The Politics of Identity and Ideology: Pakhtun Nationalism and Socialism in Pakistan - Mohmand, Abbas Khan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The article elaborates the politics of nationalism and socialism among the Pakhtuns, particularly in Khyber Pakhtunkhwa. Analyse the Pakhtun left political organizations and Movements as well as the Pakhtunistan issues, and Hashnagar pesaeants uprising. The paper led us to the banning of all left political organization including Communist Party of Pakistan, Khudai Khedmatgar and other regional nationalist and socialist organization during Cold War. The Cold War re-shaped the political dynamics in Pakistan particularly in Khyber Pakhtunkhwa and Baluchistan. Both were the Front line Provinces in the great game between the United States and the Soviet Union. When Pakistan joined the United State-led West-bloc, the SEATO and SENTO pact was signed against the Communism. Therefore, the Pakistan state took action against the left political organization in Pakistan, due to the Pakhtun socialists activated in a new mask of socialism and strongly opposed the ruling elite of Pakistan. While the nationalist cleared their stance to work for a progressive Pakistan. Both were organized and engaged with Pakistani leftists against the Pakistani ruling elite and finally they organized anti one unit front known as United Front and merged their organization and formed a national level left party, the National Awami Party. The National Awami Party was a geniune left political party all the left banned organization including nationalist and socialist joined it with the manofestation of socialism in Pakistan. However, the ideological split in the International communist movement influence the politics of National Awami Party and its leadership in Pakistan. Meanwhile the National Awami Party split into two factions Pro-Mascow and Pro-China, among the Pakhtuns the pro-China faction were eliminated by the pro-Moscow Wali Khan group from his Party. Consequently, the pro-China faction formed a new left political organization called the Mazdoor Kisan Party in 1967. However, during the 1970 election the Maoist pro China Mazdoor Kisan Party did not participated in general election and mobilized the Hashnagar peasant uprising against the landlords but many lanlords were the candidate of different poltical parties. This article analysis the unification and split in the left political wing in Pakistan and particularly in Khyber Pakhtunkhwa and overview the historical developments and events which shaped and re-shaped the nationalist and socialist tendencies among the Pakhtuns.